Prediction of Entrepreneurial Intention and Pre-Start-Up Behaviours on Entrepreneurial Concentrated Students - Fiesta Octaviani; Renaldi Renaldi; Sabrina Oktaria Sihombing (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2021)
Abstract: This study aims to examine the factors that have the potential to influence student’s entrepreneurial intentions using the TPB theory model along with several other factors (i.e., attitude towards entrepreneurship, subjective norms, perceived behavioral control, innovation, proactive personality, need for achievement, internal locus of control, risk taking propensity, lifestyle integration, social networking, resources, opportunity recognition, fungibility issues, entrepreneurial intention, and pre-start-up behavior). Data were collected through 222 entrepreneurship concentration students from well-known universities in Indonesia. The structural equation model (PLS-SEM) was applied to test the research hypotheses. The emergence of significant and positive results among all factors involved, except fungibility issues is evidence of the positive influence of the factors studied on student’s entrepreneurial intentions in Indonesia which are then briefly summarized in the form of conclusions. Keywords: Entrepreneurial intention, theory of planned behavior, pre-start-up behavior, entrepreneurship Prediksi Entrepreneurial Intention dan Pre-Start-Up Behaviour terhadap Mahasiswa Konsentrasi KewirausahaanAbstrak: Penelitian ini bertujuan untuk menguji faktor-faktor yang berpotensi mempengaruhi niat berwirausaha mahasiswa dengan menggunakan model teori TPB beserta beberapa faktor lainnya (yaitu sikap berwirausaha, norma subjektif, persepsi pengendalian perilaku, inovasi, kepribadian proaktif, kebutuhan berprestasi, internal. locus of control, kecenderungan mengambil risiko, integrasi gaya hidup, jejaring sosial, sumber daya, pengenalan peluang, masalah kesepadanan, niat kewirausahaan, dan perilaku pra-start-up). Pengumpulan data dilakukan melalui 222 mahasiswa konsentrasi kewirausahaan dari universitas ternama di Indonesia. Model persamaan struktural (PLS-SEM) digunakan untuk menguji hipotesis penelitian. Munculnya hasil yang signifikan dan positif di antara semua faktor yang terlibat, kecuali masalah kesepadanan merupakan bukti pengaruh positif dari faktor-faktor yang diteliti terhadap niat berwirausaha mahasiswa di Indonesia yang kemudian dirangkum secara singkat dalam bentuk kesimpulan.Kata kunci: Niat kewirausahaan, teori perilaku terencana, perilaku-pra-start-up, kewirausahaan